2002
DOI: 10.1103/physrevlett.88.066405
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Doping and Band-Gap Anomalies in Delafossite Transparent Conductive Oxides

Abstract: Doping wide-gap materials p type is highly desirable but often difficult. This makes the recent discovery of p-type delafossite oxides, CuM(III)O2, very attractive. The CuM(III)O2 also show unique and unexplained physical properties: Increasing band gap from M(III) = Al,Ga, to In, not seen in conventional semiconductors. The largest gap CuInO2 can be mysteriously doped both n and p type but not the smaller gaps CuAlO2 and CuGaO2. Here, we show that both properties are results of a large disparity between the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
251
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 339 publications
(282 citation statements)
references
References 23 publications
28
251
3
Order By: Relevance
“…At first glance, this seems to contradict the trend in other oxides, where the optical band gap decreases with the atomic number. Based on LAPW-LDA calculations, Nie et al 19 suggested that the observed absorption onset corresponds not to the minimum band gaps but to direct optical transitions at the L point, as the direct transitions at Γ and Z point are symmetry-forbidden. Indeed, GGA band structures for CuGaO 2 and CuInO 2 show that the conduction band minimum at the Γ point moves towards lower energies for increasing atomic number.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At first glance, this seems to contradict the trend in other oxides, where the optical band gap decreases with the atomic number. Based on LAPW-LDA calculations, Nie et al 19 suggested that the observed absorption onset corresponds not to the minimum band gaps but to direct optical transitions at the L point, as the direct transitions at Γ and Z point are symmetry-forbidden. Indeed, GGA band structures for CuGaO 2 and CuInO 2 show that the conduction band minimum at the Γ point moves towards lower energies for increasing atomic number.…”
Section: Resultsmentioning
confidence: 99%
“…Available experimental values for the optical band gaps of CuAlO 2 are quite disperse and range between 2.9 15 and 3.9 16 eV, where most studies point to a gap of 3.5-3.6 eV 4,17,18 . Theoretical studies point towards the existence of an indirect fundamental band gap that optically inactive due to symmetry reasons 19 . Indeed, evidence for such an indirect band gap was found experimentally, although the band gap size is subject to debate.…”
Section: Resultsmentioning
confidence: 99%
“…Single-particle transitions are only considered, thus electron-hole correlations are not treated and would require higher order electronic structure methods [91,92,93]. The approach has been shown to provide reasonable optical absorption spectra in comparison to experiment [94,95,96,97,89].…”
Section: Theory/calculationmentioning
confidence: 99%
“…Thus, the introduction of sensitized CuGaS 2 QDs could enhance the light harvesting ability in TiO 2 /N719, which can be attributed to the following factors: a higher intensity and a red shift of light absorption edge from 600 nm to around 700 nm. Such improvement could lead to an increased electron concentration in TiO 2 /N719 substrate sensitized with CuGaS 2 QDs [56][57][58][59][60][61][62].…”
Section: Resultsmentioning
confidence: 99%